The Importance of Follow-Up and Evaluation of Intraoperative Findings to Determine Surgical Indications for Retractile Testis - Kazuro Kikkawa; Yuko Ueda; Shimpei Yamashita; Yasuo Kohjimoto; Isao Hara (Advances in Urology)
Objectives. Ascending testis or acquired undescended testis develops in approximately 30% of cases of retractile testis, and orchiopexy is recommended for these cases. This study aimed at assessing the intraoperative anatomical findings of ascending testis and acquired undescended testis in search of better management for retractile testis. Methods. We retrospectively collected data of patients with confirmed diagnosis of retractile testis between February 2012 and November 2021. Orchiopexy was performed for cases with ascending testis and for patients with increasing difference of right and left testicular volume. The site of gubernaculum attachment and patent processus vaginalis were evaluated during surgery. Results. A total of 119 testes in 71 patients with retractile testis were included in this study. Sixteen retractile testes in 12 patients (17%) underwent orchiopexy. The weight at birth was significantly higher, and bilateral retractile testes were significantly more common in the follow-up group than in the surgical intervention group. In the surgical intervention group, the abnormal site of gubernaculum attachment was found in 12 out of 16 testes (75%), and patent PV was found in nine out of sixteen testes (56%). Sites of gubernaculum attachment in testes with patent PV were significantly higher than in sites with closed processus vaginalis, and all testes with patent processus vaginalis had abnormal site of gubernaculum attachment. Conclusion. Patients with ascending testis and acquired undescended testis have clinical features and intraoperative abnormal findings similar to a cryptorchidism. Therefore, our surgical indication for retractile testis is considered appropriate.